The EFL Lecturers’ Voices: Strategies and Concerns in Writing the Ba Thesis - Zulfikar, Teuku; Emawati; Amiruddin; Sundusiyah, Anis (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2023)
The objective of this paper is to examine the perspectives of department chairmen and lecturers who teach Research Methods in English Language Teaching (ELT) with regards to strategies employed in thesis writing. We conducted in-depth interviews to collect data. Four English Education department chairs were interviewed and 24 lecturers teaching Research Methodology in ELT via FGDs. Using coding techniques, the data from interviews and FGDs were divided into two main themes: academic and non-academic variables to successful thesis writing. Academic variables include the selection of research problems, analysis of prior relevant themes, formulation of research questions, and comprehension of writing styles. In addition, participants acknowledged that non-academic variables play a vital role in the successful writing of a thesis. The participants highlighted time management and interpersonal relationships as non-academic issues.